KEARIFAN LOKAL DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI (KAJIAN SOSIOLOGI SASTRA) - Anisa Disma Cahyana Sukri Pertiwi; Eko Cahyo Prawoto (Buana Bastra, 2020)
In this ressearch, the aim of this ressearch is (1) describe the aspects of welfare, (2) to describe the aspects of peace. The method used is descriptive qualitative and sociology of literature and uses the object of aspects of welfare and aspects of peace in the novel Genduk by Sundari Mardjuki. Data collection techniques, namely reading over and over, marking data, and recapitulating data. Data analysis techniques use categorizing and creating tables. The validity of the data used the validity test, data reliability and stability test. This study uses the theory of Robert Siabrani. Local wisdom has two aspects, namely, the welfare aspect and aspects of peace. The daata source used is thhe novel Genduk by Sundari Mardjuki. The research data is the form of quootations. The results of research on Sundari Mardjuki's novel Genduk show that the environment in the story is set in the 1970s. The Genduk and Yung characters live in Ringinsari Village, near Mount Sindoro. In the story of the character Yung, the way to ask God is very different, the character Yung always uses chanting from ancient times. The village still preserves its culture, such as Among Thickness, Kenduri, Jatilan, and cutting hair from the spikes.